The Text of an Unapproved Treaty between Byzantium and the Venice, 1265 - Yevgeniy Aleksandrovich Khvalkov (Античная древность и средние века, 2019)
After the re-establishment of the Byzantine Empire, there were several attempts of establishing the diplomatic relations with the Republic of Venice. One the one hand, Venice lost in 1261 its most remote outpost of the colonial empire, and this was a real shock for the doge and the ruling elite. However, thinking in the realistic terms, Venetians preferred securing the guarantees of the peaceful existence within the Byzantine Empire to the attempts of re-conquest. On the other hand, Emperor Michael VIII Paleologue was soon disappointed by his former allies, namely Genoese. Being informed about the Latin’s plot in Constantinople with the participation of the Genoese, the Emperor exiled the later to the metropolis. This pushed him towards the normalization of the relations with the Venetians. The negotiations began in late 1264, and faced many obstacles. Even though the conditions proposed by Michael VIII were more than generous, the Republic of Saint Mark declined the first draft of the treaty. This article addresses the text of this draft.